Effects of coenzyme Q10 on semen cryopreservation of stallions classified as having good or bad semen freezing ability - Carneiro, Joao A.M. [UNESP]; Canisso, Igor F.; Bandeira, R. S. [UNESP]; Scheeren, V. F.C. [UNESP]; Freitas-Dell'Aqua, Camila P. [UNESP]; Alvarenga, Marco A. [UNESP]; Papa, Frederico O. [UNESP]; Dell'Aqua, Jose A. [UNESP] (Elsevier, 2018)
This study aimed to evaluate the antioxidant properties of coenzyme Q10 (CoQ10) during cryopreservation of semen obtained from stallions having good and bad semen freezing ability (GFA vs. BFA, respectively). Forty ejaculates (n = 20 stallions) were split into five centrifugation and five freezing extenders containing different concentrations of CoQ10 (0, 25, 50, 75 and 100 μmols/L). If CoQ10 was added to the centrifugation extender, the freezing extender had no CoQ10 added; similarly, if CoQ10 was added to the freezing extender, the centrifugation extender had no CoQ10. Semen cryopreserved on extenders containing no CoQ10 served as the control. After post-thaw total sperm motility (TM) assessments, the stallions were classified as GFA (i.e., decrease of ≤25% in TM, n = 7) or BFA (i.e., decrease of ≥40% in TM, n = 5). Stallions not fitting (n = 8) this enrollment criteria had samples discarded. After that, two straws for each extender were thawed at 37 °C for 30 s; one straw was immediately used for evaluation of sperm kinetics, plasma membrane integrity, non-capacitated spermatozoa, reactive oxygen species production, mitochondrial activity and lipid peroxidation. The second straw was kept at 37 °C for 30 min and subjected to the same assessments. Expectedly, sperm motility parameters were significantly lower for stallions with BFA. There were no effects of CoQ10 concentration or time for all parameters evaluated in the group with GFA when compared with the control extender (p > 0.05), except lipid peroxidation (p < 0.05). However, stallions with BFA had improved sperm parameters for samples processed with extenders containing CoQ10 (particularly 75 μmols/L) (p < 0.05), except for the reactive oxygen species production and mitochondrial potential (T0) in which there were no differences between the groups (p > 0.05). In summary, 75 μmols/L appears to be the optimal dose of Co-Q10, particularly, when added to the centrifugation extender.
Keywords: Antioxidant; Cryodamage; Horse; Oxidative stress; Semen freezing